Wild animals study group (CCAE-UFES): A tool to kowledge amplification, networkformation and educational actions - Lopes Andrade, Wanderson; Mantovani Cezana, Jórnie; Barbosa Amaral, Camila (Guará Journal, 2022)
The Veterinary Medicine program at UFES is the only one affiliated with a federal public higher education institution in the state. This fact, coupled with the growing demand for knowledge about wild animals, led to the establishment of the Wild Animal Study Group. Since then, it has held symposia, conferences, lectures, and discussions to achieve this goal, in addition to serving as an intermediary between students and graduates, disseminating knowledge to society. Despite facing challenges, the group's importance has been recognized on campus. This paper aims to report some of the activities carried out throughout its existence, until its cancellation in 2019, and how these actions relate to current and relevant topics within the field of Wild Animal Veterinary Medicine.
Keywords: Wild animals; Education; Graduation students; Society